Simulation and experimental evaluation on a skyhook policy-based fuzzy logic control for semi-active suspension system. (27th June 2011) - Hudha, Khisbullah; Jamaluddin, Hishamuddin
This paper focuses on performance evaluation of several outer loop controller designs employed in a quarter car suspension featuring a magnetorheological fluid damper. A Magne-Ride damper was employed and its behaviour was investigated in the form of force-displacement and force-velocity characteristics. The non-linear hysteretic behaviour of the damper was modelled using a sixth order polynomial model. Force tracking control was performed to check the force tracking ability of the damper using a PI control. The governing equations of motions were formulated and integrated with skyhook control. Skyhook policy was then adapted in the development of a fuzzy logic control to enhance the ride performance. The performance of fuzzy logic control was compared with the on-off and continuous skyhook control in time domain. The results show that skyhook algorithm-based fuzzy logic control gives better performances than its counterparts.